2014
DOI: 10.1002/2014jc009897
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of variability in Arctic sea‐ice drift speed

Abstract: We explore the main drivers of seasonal and long-term variations in basin-scale Arctic sea-ice drift speed. To do so, we examine the relationship between the observed time-varying area-mean ice drift speed in the central Arctic and observed thickness and concentration as well as surface wind stress. Drift speeds are calculated from the positions of drifting buoys, thickness is based on submarine observations, concentration on satellite observations, and the wind stress comes from a global reanalysis. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 57 publications
4
68
1
Order By: Relevance
“…Consequently, we show that the finding by Haumann [] and Holland and Kwok [] that ice drift changes (Figure e) are induced by wind changes (Figure c), is also evident over the period 1979 to 2011. Potential inconsistencies in the drift trend [ Fowler et al , ; Olason and Notz , ] do not affect these results qualitatively (Figure S1 in the supporting information). The increased northward drift in the Ross Sea causes a higher sea ice production at the coast, a higher northward advection, thus an expansion and concentration increase at the ice edge.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we show that the finding by Haumann [] and Holland and Kwok [] that ice drift changes (Figure e) are induced by wind changes (Figure c), is also evident over the period 1979 to 2011. Potential inconsistencies in the drift trend [ Fowler et al , ; Olason and Notz , ] do not affect these results qualitatively (Figure S1 in the supporting information). The increased northward drift in the Ross Sea causes a higher sea ice production at the coast, a higher northward advection, thus an expansion and concentration increase at the ice edge.…”
Section: Resultsmentioning
confidence: 99%
“…This is highest in summer, decreasing steadily from August to January, when it plateaus until April and then starts increasing again. Ólason and Notz (2014) found that over the 33 years they considered, the observed drift speed depends on concentration when concentration is low, thickness when concentration is high, and is related to an increased number of active fractures in AprilMay. It is not clear how well our model captures this relationship since the results for only 1 year can be heavily influenced by the timing and intensity of storms passing through the region.…”
Section: Evaluation Of Simulated Sea Ice Drift and Sensitivity To Thementioning
confidence: 97%
“…An analysis of such observations for the years 1979-2001 found summer speeds generally less than or equal to $5 cm s 21 [Martin and Gerdes, 2007]. However, more recent studies indicate a rapid acceleration of arctic sea ice floes [Rampal et al, 2009] to values closer to $12 cm s 21 at the end of summer [Spreen et al, 2011] or 8 km/d in winter [Olason and Notz, 2014].…”
Section: 1002/2015jc011182mentioning
confidence: 99%